ANALISIS LAPORAN KEUANGAN UNTUK MENINGKATKAN KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PADANG PANJANG (ANALSIS KINERJA BERDASARKAN PERMENDAGRI NO 47 TAHUN 1999) - Febri, Arinal; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to explain performance of the Perusahaan Daerah Air Minum (PDAM) Padang Panjang city from monetary aspect based on Ministry Home Affairs’s decision No. 47th of 1999. This research uses secondary data, namely company financial report. Collected data technique used interviews and documentation. Analysis data technique used with collected and classify financial report data and review or analyze to company’s performance.Based on the results of the analysis of the financial data of the Perusahaan Daerah Air Minum (PDAM) Padang Panjang City in 2015-2019 which was reviewed from the Ministry of Home Affairs No. 47 of 1999. In 2015 it was in a poor performance, in 2016 it obtained a fairly good performance, in 2017 it obtained a poor performance, in 2018 the performance was in a poor performance, and in 2019 the performance was fairly good. So, overall the 5-year research period obtained a poor performance score.Keywords :  Financial aspect, company’s performance, Ministry of Home Affairs No. 47 of 1999